(untitled) (Anais do Salão Inovação, Ensino, Pesquisa e Extensão, 2020)
Numerous industries use dyes to obtain their products, generating a considerable volume of colored effluent. From this, the need arises to develop new forms of treatment suitable for these effluents. Thus, the present work aimed to perform the synthesis and characterization of graphene-based three-dimensional materials, using an environmentally friendly route, with low cost and high yield, and to determine their efficiency in removing methylene blue from water. The synthesis of the materials was performed by reducing graphene oxide under particular conditions using a thermochemical route. The effects of different amounts of ascorbic acid as a reducing agent were tested and compared with a material synthesized under the same conditions but without the addition of reducing agents. The adsorption study was performed in test tubes, where approximately 10 mg of adsorbent and 5 mL of methylene blue solution at a concentration of 5 mg.L-1 were added. The tubes were agitated in the dark for 48h at 22°C. At the end of the agitation time, the final concentration of the samples was determined by UV-Vis spectrophotometry, obtaining the adsorption efficiency. The synthesis methodology used resulted in materials with a well-defined interconnected three-dimensional porous network. Variations in the amount of reducing agent promoted significant morphological changes, and spectroscopy data showed important structural changes according to the concentration of reducing agent. The methylene blue adsorption study showed that the material has a removal efficiency of up to 92,8% for materials with lower levels of reducing agent. As the amount of reducing agent increases, the removal efficiency decreases, possibly due to the presence of the remaining ascorbic acid from the synthesis. Also, the synthesized material, without the addition of the reducing agent, due to the presence of remaining oxygenated functional groups, presented lower removal efficiency. The excellent adsorption rate is attributed to chemical adsorption through strong π- π stacking interactions in addition to the mesoporous structure of the materials. The results show that materials can be applied to remove pollutants, as dyes, from water, helping to access drinking water and quality.